Intercultural Communication Challenges in the Period of the Novel Coronavirus (Covid-19) (The Case of Qatar Airways) - Kublashvili, Margo (European Scientific Journal, ESJ, 2021)
Under the conditions of the global threat of the modern world - the novel coronavirus (Covid-19) pandemic, the demand for social distancing as a commonly proven method of preventing fatal cases and stopping the virus has fundamentally changed the process of communication in an intercultural environment. Our research aims to study the impact of the pandemic on the intercultural communication process and its quality in a multicultural environment. Cabin Crew of Qatar Airways, as one of the largest multicultural/multinational companies, was selected as a target group. A qualitative method of data collection – interviewing – was used as a research technique. In particular, the target group was interviewed through a semistructured questionnaire – by a so-called "narrative interview" method. This research enabled us to obtain new narratives which were created on the coronavirus background – responses of the Qatar Airways Cabin Crew and the company's international passengers to the challenge of Covid-19. The study and analysis of these responses revealed that representatives of different cultures (Individualistic/Collectivist cultures, High/Low uncertainty avoidance cultures, Submissive orientation/Mastery orientation cultures, Tight/Loose cultures) have different attitudes towards the pandemic as an uncertain and unpredictable future; towards the Covid-19 vaccine; towards wearing a mask and eye contact related to it; in addition, they can be distinguished by different perceptions of territorialism as personal space (physical and social distancing); different feelings of fear and anxiety and readiness to obey/disobey introduced rules or restrictions (so-called Lockdown, Curfew). According to the research, these differences are due to the "mental program" of a society, i.e. a purely cultural factor. However, despite several intercultural differences, daily contact with groups having other cultures significantly increases opportunities for collaboration, which, in times of crisis, does not hinder the process of interaction between different cultures, but on the contrary, it increases the level of intercultural acceptance and sensitivity.